2010
DOI: 10.1080/17588921003759934
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal temporal perception deficits in a patient with left spatial neglect

Abstract: We examined multisecond time estimation (up to 60 s) for visual and auditory events in a patient with left spatial neglect (RR), who grossly underestimated all durations in all tasks. In contrast, healthy controls and a patient with left hemisphere damage (HW) demonstrated accurate estimates of the same durations. These findings add to a growing body of literature suggesting that neglect cannot be understood simply in terms of a bias in orienting attention to one side of space. In addition, these data suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…We make the hypothesis that this difficulty might be explained by the temporal processing impairments demonstrated by neglect patients (Berberovic et al, 2004; Danckert et al, 2007; Merrifield et al, 2010). Patients tend to underestimate multisecond intervals: Danckert et al (2007) tested neglect patients in a temporal estimation task.…”
Section: Neglect As a Disorder Of Generating And Updating Mental Modelsmentioning
confidence: 93%
See 1 more Smart Citation
“…We make the hypothesis that this difficulty might be explained by the temporal processing impairments demonstrated by neglect patients (Berberovic et al, 2004; Danckert et al, 2007; Merrifield et al, 2010). Patients tend to underestimate multisecond intervals: Danckert et al (2007) tested neglect patients in a temporal estimation task.…”
Section: Neglect As a Disorder Of Generating And Updating Mental Modelsmentioning
confidence: 93%
“…A trial could last 5, 15, 30, and 60 s and patients were asked how long the clockwise motion lasted on each trial. The authors found that neglect patients underestimated all durations, showing an impairment for estimating the passage of time: even for trials that lasted 60 s, neglect patients reported that the clockwise motion was present for no longer than 10 s. Those deficits have also been found in the processing of auditory stimuli (Cusack et al, 2000; Merrifield et al, 2010). …”
Section: Neglect As a Disorder Of Generating And Updating Mental Modelsmentioning
confidence: 96%
“…However, neglect is also associated with deficits that are not obviously spatial, for example working memory impairments (Danckert & Ferber, 2006), increased attentional blink duration (Husain, Shapiro, Martin, & Kennard, 1997) and impaired temporal estimation (Danckert et al, 2007;Merrifield, Hurwitz, & Danckert, 2010). We have suggested Shaqiri, Anderson, & Danckert, 2013) that performance on such tasks is an indirect reflection of impaired systems for learning environmental probabilities (Shaqiri & Anderson, 2012) and failing to update them when they change .…”
Section: Introductionmentioning
confidence: 95%
“…For example, one domain that has not been explored to any great extent (at least to our knowledge) is the influence of prism adaptation on non-spatially lateralized deficits in neglect such as SWM (Husain et al, 2001; Ferber and Danckert, 2006), time estimation (Danckert et al, 2007; Merrifield et al, 2010), and sustained-temporal attention (Husain et al, 1997). There is some controversy as to whether these deficits should be considered core symptoms of neglect (Danckert and Ferber, 2006), or viewed merely as exacerbating factors (Husain and Rorden, 2003).…”
Section: Prism Adaptation and Neglectmentioning
confidence: 99%
“…More recent studies have shown that neglect is a heterogeneous disorder comprised of a constellation of deficits including impaired temporal allocation of attention (Husain et al, 1997), poor time perception (Danckert et al, 2007; Merrifield et al, 2010; Oliveri et al, 2013), and spatial working memory (SWM) impairments evident throughout visual space (Husain et al, 2001; Ferber and Danckert, 2006). We will argue here that the deficits in SWM represent a core component of the disorder and as such, should be a target for rehabilitative strategies.…”
mentioning
confidence: 99%